KEANEKARAGAMAN VEGETASI DI HUTAN LINDUNG GUNUNG SEMAHUNG DESA SAHAM KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Novianti, .; Anwari, M Sofwan; Wulandari, Reine Suci (Universitas Tanjungpura, 2017)
Efforts to inventory the wealth of forest resources are still needed. There are stillmany areas that have potential especially plants than can be utilezed in order to preserver the forest. This research aims to determine the Diversity of Vegetation that exist in the Protected Forest of Gunung Semahung, Village of Saham, Sengah Temila Sub-district, Landak District. This research uses survey method by placing double plot where sampling is placed in accordance with the predetermined direction. The research plots are systematically laid out. Number of paths made as lines with a length of 1000 meters, each path there are 25 plot observations made in accordance with the direction of the compass, so the overallarea is 2 Ha. 20 x 20 m observation plot to measure tree level, 10 x 10 m for measuring pole level, 5 x 5 m for measuring stake level and 2 x 2 m to measure seedling level. The distance between plots is 20 m. The data obtained are then calculated relative density and density, relative frequency and frequency, dominance and relative dominance, to obtain an Important Value Index (INP). Further calculated Dominance Index (C), Type Diversity Index (H) and Tpe Abudance Index (E). The Important Value Index (INP) at the dominant seedling level is Garcinia xanthochymus (16,39). The Important Value Index (INP) at the most dominant stakes is the Durio zibethinus (15,68). The Important Value Index (INP) at the most dominant pole level is the Shorea acuminatissima (19,59). The Important Value Index (INP) at the most dominant tree level is the Diosphyros maingayi (36,36). The highest Dominity Index at the tree level is 0,1747. The highest Diversity Index at the stakes level is 1.5510. The highest Type Abundance Index at the pole level is 0.9625.Keywords: Mount Semahung, The Diversity Of Vegetation Protected Forest, The Index Values Are Important